The transporters SLC35A1 and SLC30A1 play opposite roles in cell survival upon VSV virus infection - Anna Moskovskich (Nature Portfolio, 2019)
Abstract Host factor requirements for different classes of viruses have not been fully unraveled. Replication of the viral genome and synthesis of viral proteins within the human host cell are associated with an increased demand for nutrients and specific metabolites. With more than 400 acknowledged members to date in humans, solute carriers (SLCs) represent the largest family of transmembrane proteins dedicated to the transport of ions and small molecules such as amino acids, sugars and nucleotides. Consistent with their impact on cellular metabolism, several SLCs have been implicated as host factors affecting the viral life cycle and the cellular response to infection. In this study, we aimed at characterizing the role of host SLCs in cell survival upon viral infection by performing unbiased genetic screens using a focused CRISPR knockout library. Genetic screens with the cytolytic vesicular stomatitis virus (VSV) showed that the loss of two SLCs genes, encoding the sialic acid transporter SLC35A1/CST and the zinc transporter SLC30A1/ZnT1, affected cell survival upon infection. Further characterization of these genes suggests a role for both of these transporters in the apoptotic response induced by VSV, offering new insights into the cellular response to oncolytic virus infections.